2016
DOI: 10.1002/ece3.2382
|View full text |Cite
|
Sign up to set email alerts
|

Models of Eucalypt phenology predict bat population flux

Abstract: Fruit bats (Pteropodidae) have received increased attention after the recent emergence of notable viral pathogens of bat origin. Their vagility hinders data collection on abundance and distribution, which constrains modeling efforts and our understanding of bat ecology, viral dynamics, and spillover. We addressed this knowledge gap with models and data on the occurrence and abundance of nectarivorous fruit bat populations at 3 day roosts in southeast Queensland. We used environmental drivers of nectar producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 89 publications
(110 reference statements)
1
49
1
Order By: Relevance
“…As such, the results indicate that the density of flying fox roosts, rather than the population density of flying foxes, is associated with HeV spillover. This agrees with the findings of Giles et al ., who found that the presence of more smaller camps was associated with spillover. Similarly, a study on the roost characteristics of P. medius in Bangladesh noted more roosts, but not more bats, in villages reporting NiV cases, and that increased numbers of smaller roosts and human disease were associated with forest fragmentation .…”
Section: Changing Resource Landscapes and Henipavirus Spilloversupporting
confidence: 93%
See 2 more Smart Citations
“…As such, the results indicate that the density of flying fox roosts, rather than the population density of flying foxes, is associated with HeV spillover. This agrees with the findings of Giles et al ., who found that the presence of more smaller camps was associated with spillover. Similarly, a study on the roost characteristics of P. medius in Bangladesh noted more roosts, but not more bats, in villages reporting NiV cases, and that increased numbers of smaller roosts and human disease were associated with forest fragmentation .…”
Section: Changing Resource Landscapes and Henipavirus Spilloversupporting
confidence: 93%
“…However, theoretical models provide a range of predictions for the consequences of urban habituation on the distribution of pathogen across bat populations. Resource shifts from habitat loss or resource provisioning that changes flying fox site fidelity and migratory behavior or stopover patterns could also influence HNV prevalence in bat populations and spillover risks . For pathogens with long infectious periods relative to bat movement rates, urban colonization could spread pathogens across new areas near humans and domestic animals.…”
Section: Changing Resource Landscapes and Henipavirus Spillovermentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence suggests that HeV spillover is related to climate by several different mechanisms acting at different temporal and spatial scales. From broad to fine: the spatial and temporal abundance patterns of HeV reservoir hosts, flying foxes, are related to climatic suitability (Martin et al 2016); the spatial dynamics of bats are largely governed by food resources that are dependent on climate (Hudson et al 2010; Giles et al 2016); the levels of HeV shedding may be linked to low food productivity and availability after severe weather events (Plowright et al 2008; McFarlane et al 2011; Páez et al 2017; Peel et al 2017); and lastly HeV survival in microclimates which might facilitate indirect transmission, is also dependent on climate (Martin et al 2015, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, temperature dependent survival, as estimated here, is more likely to be the best case survival scenario and an overestimate. This means that the poor contribution of HeV survival towards predicting its spillover [11] ■ could be caused by its susceptibility to the conditions that occur in microclimates, and the stronger effect that temperature has on other processes that influence HeV spillover risk like bat densities and Eucalyptus phenology [28, 29] ■ .…”
Section: Discussionmentioning
confidence: 99%